Trauma induces expansion and activation of a memory‐like Treg population. Issue 3 (12th June 2020) - Yamakawa, Kazuma; Tajima, Goro; Keegan, Joshua W.; Nakahori, Yasutaka; Guo, Fei; Seshadri, Anupamaa J.; Cahill, Laura A.; Lederer, James A.
Abstract: CD4+ regulatory T cells (Tregs) are acutely activated by traumatic injury, which suggests that they may react to injury with similar kinetics as memory T cells. Here, we used a mouse burn trauma model to screen for memory‐like T cell responses to injury by transferring T cells from sham or burn CD45.1 mice into CD45.2 mice and performing secondary injuries in recipient mice. Among all T cell subsets that were measured, only Tregs expanded in response to secondary injury. The expanded Tregs were a CD44 high /CD62L low subpopulation, markers indicative of memory T cells. CyTOF (cytometry by time‐of‐flight) mass cytometry was used to demonstrate that injury‐expanded Tregs expressed higher levels of CD44, CTLA‐4, ICOS, GITR, and Helios than Tregs from noninjured mice. Next, we tested whether a similar population of Tregs might react acutely to burn trauma. We observed that Tregs with a phenotype that matched the injury‐expanded Tregs were activated by 6 h after injury. To test if Treg activation by trauma requires functional MHC class II, we measured trauma‐induced Treg activation in MHC class II gene deficient (MHCII −/− ) mice or in mice that were given Fab fragment of anti‐MHC class II antibody to block TCR activation. Injury‐induced Treg activation occurred in normal mice but only partial activation was detected in MHCII −/− mice or in mice that were given Fab anti‐MHCII antibody. These findings demonstrate that trauma activates a memory‐like Treg subpopulation and that Treg activation by injury is partially dependent on TCR signaling by an MHC class II dependent mechanism. Graphical Abstract: Traumatic injury stimulates specific expansion of a CD4+ CD44high Treg subpopulation that shows enhanced reactivity to secondary injury much like a memory T cell.